The association between paired basic amino acid cleaving enzyme 4 gene haplotype and diastolic blood pressure - 李建平 王晓滨 陈常忠 徐新 洪雪梅 徐希平 高炜 霍勇 (Chinese medical journal, 2004)
Background In a previously identified locus linked to hypertension on chromosome 15q, we identified three blood pressure candidate genes : insulin-like growth factor 1 receptor gene (IGF1R), myocyte specific enhancer factor 2A gene (MEF2A), and paired basic amino acid cleaving enzyme 4 gene (PACE4). In this study, we tested their associations with hypertension using haplotype analysis. Methods A total of 288 unrelated individuals, including 163 high diastolic blood pressure (DBP) subjects and 125 normal DBP subjects were enrolled in this case-control study. Twenty single nucleotide polymorphisms (SNPs) in the three genes were genotyped using polymerase chain reaction followed by restriction enzyme digestion. Haplotype analysis was accomplished in the following stages. (1) pair-wise linkage disequilibrium test among SNPs on the same gene was performed to explore blocks in which recombination is very unlikely to happen; (2) Estimation-Maximization algorithm was applied to estimate haplotype frequencies in each block; (3) the chi-square test was used to examine the specific haplotype difference, and a permutation test was used to examine the overall haplotype profile difference between cases and controls in each block. Results An estimated haplotype "CCCCG" frequency in the haplotype block on the PACE4 gene was significantly higher in high DBP cases than in controls (P<0.01). The overall estimated haplotype profile in this block was also significantly different between the cases and the controls (P<0.001). This association indicates. Conclusions This study for the first time demonstrated that PACE4 gene may play an important role in the regulation of DBP. This association indicates that variations influencing DBP resides in or near this genomic region.